Merging konjac glucomannan with other copolymeric hydrogels as a cutting-edge liquid raft system for dual delivery of etoricoxib and famotidine - Nabil A. Shoman; Marwa Saady; Mahmoud Teaima; Rehab Abdelmonem; Mohamed A. El-Nabarawi; Sammar Fathy Elhabal (Taylor & Francis Group, 2023)
AbstractThis study aimed to formulate and evaluate a floating raft system for the co-delivery of etoricoxib (ETO) and famotidine (FAM) using a combination of glucomannan with natural/semi-synthetic polysaccharides. Formulation variables affect gelation lag time (GLT), floating lag time (FLT), and release percentage of drugs after 1-8 h, Stability, and viscosity parameters were evaluated. In vivo X-ray studies, followed by the pharmacokinetic study, were performed on human volunteers. Formulations exhibited pseudoplastic behavior for ease of swallowing. The optimum raft system (ORS) comprised 1% Na alginate, 0.1% Low Methoxyl (LM) pectin, 0.8% Konjac glucomannan (KGL), 1% Precirol, and 1% CaCO3. ORS exhibited rapid GLT and FLT (around 42 and 8 sec respectively) in 0.1 N HCl as well as controlled release of ETO (15% in 1 h and 82% in 8 h) and FAM (29% in 1 h and 85% in 8 h). Formulation stability with the absence of any drug-excipient interactions was observed. The X-ray imaging showed a promising buoyancy ability for approximately 8 h. Compared with marketed products, ORS showed superior relative bioavailability for both drugs. These findings revealed the successful preparation of a promising raft system with improved dual drug delivery.